Pengaruh Perilaku Merokok, Konsumsi Alkohol dan Hiburan Malam Terhadap Risiko Penggunaan Narkotika - Akhmad Azmiardi (Faletehan Health Journal, 2020)
Drug abuse in adolescence continues to increase every year. the entry of narcotics among high school students until now has been almost unavoidable because of threats, obstacles, and disturbances outside of school lurking all the time, such as the dangers of smoking, liquor, nightclubs. The purpose of this study was to determine the relationship between smoking behavior, alcohol consumption and night entertainment on the risks of using narcotics. This research is a cross-sectional study with 278 students taken by a proportional random sampling technique. The dependent variable in this study is the risk of narcotics use while the independent variables in this study include cigarette behavior, alcohol consumption, and night entertainment. Research instruments using questionnaires and data analysis using the Chi-Square test. The results found that there was a relationship between smoking behavior, drinking alcoholic behavior and the behavior of visiting night entertainment venues to the risk of narcotics use (p = <0.001). Good regulations are needed to regulate the circulation of cigarettes, alcoholic drinks and age restrictions on visitors of night entertainment to reduce the risk of narcotics use.